Cosegregation of serum cholesterol with cholesterol intestinal absorption markers in families with primary hypercholesterolemia without mutations in LDLR, APOB, PCSK9 and APOE genes. (March 2016) - Baila-Rueda, Lucía; Pérez-Ruiz, María Rosario; Jarauta, Estíbaliz; Tejedor, María Teresa; Mateo-Gallego, Rocío; Lamiquiz-Moneo, Iztiar; de Castro-Orós, Isabel; Cenarro, Ana; Civeira, Fernando
Abstract: Background and aim: The genetic cause and pathogenic mechanism of approximately 20–40% of autosomal dominant hypercholesterolemias (ADH) are unknown. Increased cholesterol intestinal absorption has been associated to ADH. If this variation contributes to their pathogenesis is unknown. Methods and results: We studied cholesterol absorption (phytosterols and cholestanol serum concentrations) and cholesterol synthesis (desmosterol serum concentration) in 20 families with ADH without causal mutations in LDLR, APOB, PCSK9 or APOE genes (non-FH ADH) selected from 54 non-FH ADH probands with (non-cholesterol sterol concentrations above 75th percentile) and without (under 75th percentile) hyperabsorption. The concentrations of cholestanol, sitosterol, campesterol and stigmasterol were higher in affected than in non-affected subjects ( p = 0.003, <0.001.<0.001, 0.002, respectively). There was a strong cosegregation of hyperabsorption with high LDL cholesterol within hyperabsorber families with odds ratio 6.80 (confidence interval 1.656–27.9), p = 0.008. In hyperabsorber families, 60.5% of subjects were hyperabsorbers and 76% of them had high LDL cholesterol versus 38.3% and 63% in non-hyperabsorber families, respectively. Conclusion: Most hypercholesterolemic family members with a hyperabsorber proband are hyperabsorbers. These absorption markers are significantly and positively associated with LDL cholesterol, and predispose to high LDL cholesterol in family members. Our data suggest that complex interindividual variation in cholesterol absorption is involved in many non-FH ADH. Highlights: Cholesterol absorption is increased in non-FH hypercholesterolemic families. Cholesterol absorption serum markers are positively associated with LDL-cholesterol. Hyperabsorption in affected families does not suggest a monogenic defect. Sterol absorption variation is involved in non-FH hypercholesterolemia pathogenesis.